Effect of pin tool design on the material flow of dissimilar AA7075-AA6061 friction stir welds - Hasan, M.M.; M., Ishak; M. R. M., Rejab (IOP Publishing Ltd, 2017)
Tool design is the most influential aspect in the friction stir welding (FSW) technology. Influence of pin tool geometry on material flow pattern are studied in this work during the FSW of dissimilar AA7075 and AA6061 aluminium alloys. Three truncated pin tool profiles (threaded, threaded with single flat, and unthreaded with single flat) were used to prepare the weldments. The workpieces were joined using a custom-made clamping system under 1100 rpm of spindle speed, 300 mm/min of traverse rate and 3° of tilt angle. The metallographic analysis showed that defect-free welds can be produced using the three pin tools with significant changes in the mixing stir zone structure. The results declared that the introducing of the flat on the cone of the probe deviates the pattern of the onion rings without changing the chemical composition of the created layers. This in turn improves the hardness distribution and tensile strength of the welded joint. It was also noted that both heat affected zone (HAZ) and thermal-mechanical affected zone (TMAZ) are similar in composition to their corresponding base materials (BM).